Application of Bump-effects in a Postprocessing step - Tao, Anthony; Gideflod, Marcus (My University, 2022)
With the rise of internet shopping, the importance of Computer-generated Imagery is rapidly increasing. Visualizations help companies sell their product, especially customizable ones such as bathroom interiors. Such applications must provide images with a degree of realism that accurately represents the real features of the product, but also be able to produce them within an acceptable time frame. A common way of producing realistic visualizations of products is using path-tracing, but for interactive applications, the technique is overly time-consuming. Still, it can function well as an offline method by pre-rendering images to be used on demand. However, with customizable products it is not a feasible solution as the permutations would quickly lead to an unimaginable amount of images. This thesis focuses on customizing bumps on the surface of walls and applying it as a post-process to avoid the permutation issue. The 3D scene will not be available during run-time, meaning information has to be stored beforehand. The proposed method simply accepts a bump map and computes the new shading as a result of new normals. The method only considers direct lighting where the camera position is static, but includes realistic soft shadows from static geometry. The resulting images’ visual quality comes close to a ray-traced image, but without further optimizations the method does not meet the required render time for larger scenes. The reasons for this are discussed, and ideas for improvement are suggested.
Keywords: Computer graphics; Master thesis; Post-process; Shadow masks; Bump effects; Soft shadows